2020
DOI: 10.1038/s41387-020-00134-z
|View full text |Cite
|
Sign up to set email alerts
|

Gynura divaricata exerts hypoglycemic effects by regulating the PI3K/AKT signaling pathway and fatty acid metabolism signaling pathway

Abstract: Objectives: The study aimed to examine the anti-diabetic effects of Gynura divaricata (GD) and the underlying mechanism. Methods: Information about the chemical compositions of GD was obtained from extensive literature reports. Potential target genes were predicted using PharmMapper and analyzed using Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO). To validate the results from bioinformatics analyses, an aqueous extract of GD was administered to type 2 diabetic rats established by feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…In addition, the studies have also shown that impaired liver function is associated with T2DM [ 32 ]. And CREA [ 33 ], WBC [ 34 ], and MCHC [ 35 ] are also related to T2DM. Therefore, the application of these parameters in the model appears to be well-founded.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the studies have also shown that impaired liver function is associated with T2DM [ 32 ]. And CREA [ 33 ], WBC [ 34 ], and MCHC [ 35 ] are also related to T2DM. Therefore, the application of these parameters in the model appears to be well-founded.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the molecular docking results of VEGF also suggest that the binding between the important components described above and VEGF is good. Many studies (Xu et al 2015 , 2020 ; Yi et al 2016 ) have shown that GD has a good curative effect on diabetes, but few studies have been performed on its specific effect on foot complications and other complications of diabetes. This study showed that the target protein of GD in the treatment of DF was VEGF, which caused changes in the serum levels of IL-6 and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the studies have also shown that impaired liver function is associated with type 2 diabetes [30]. And CREA [31], WBC [32] and MCHC [33] are also related to type 2 diabetes. Therefore, the application of these parameters in our model appears to be well-founded.…”
Section: Discussionmentioning
confidence: 99%